Refugees’ Debit Cards, Subjectivities, and Data Circuits: Financial-Humanitarianism in the Greek Migration Laboratory - Martina Tazzioli (International Political Sociology, 2019)
This article focuses on the financialisation of refugee humanitarianism in Greece, bringing attention to the Cash Assistance Programme, which is the first EU-funded project in Europe of financial support to asylum seekers, coordinated by UNHCR. It deals with three aspects. First, it focuses on the peculiar political technologies of government that it enforces, bringing attention to the modes for governing refugee population in transit. Then, it moves on by analysing the effects of subjectivation produced by temporary and exclusionary mechanisms of financial support, together with the forms of value extraction that stem from it. It argues that to be at stake are modes of temporary incorporation into the financial circuits that push migrants to act as if they were citizens and consumers, therefore playing on a fictional dimension. Third, it takes into account the data circulation activities that are connected to it, analysing what I call the circuits of financial humanitarianism and explaining in detail how data is shared between the different actors involved. In the final part, the article centres on the antinomies between freedom and autonomy, highlighting how the notion of autonomy has been appropriated by international organisations, such as the UNHCR, as well as in refugee studies literature, to craft and justify measures of containment that are supported by the use of digital technologies.